The habenula clock influences response to a stressor - Adriana Basnakova; Ruey-Kuang Cheng; Joanne Shu Ming Chia; Giuseppe D'Agostino; Suryadi; Germaine Jia Hui Tan; Sarah R. Langley; Suresh Jesuthasan (Neurobiology of Stress, 2021)
The response of an animal to a sensory stimulus depends on the nature of the stimulus and on expectations, which are mediated by spontaneous activity. Here, we ask how circadian variation in the expectation of danger, and thus the response to a potential threat, is controlled. We focus on the habenula, a mediator of threat response that functions by regulating neuromodulator release, and use zebrafish as the experimental system. Single cell transcriptomics indicates that multiple clock genes are expressed throughout the habenula, while quantitative in situ hybridization confirms that the clock oscillates. Two-photon calcium imaging indicates a circadian change in spontaneous activity of habenula neurons. To assess the role of this clock, a truncated clocka gene was specifically expressed in the habenula. This partially inhibited the clock, as shown by changes in per3 expression as well as altered day-night variation in dopamine, serotonin and acetylcholine levels. Behaviourally, anxiety-like responses evoked by an alarm pheromone were reduced. Circadian effects of the pheromone were disrupted, such that responses in the day resembled those at night. Behaviours that are regulated by the pineal clock and not triggered by stressors were unaffected. We suggest that the habenula clock regulates the expectation of danger, thus providing one mechanism for circadian change in the response to a stressor.